The Malaysian Public-Private Partnership (PPP): Financing the Tolled Highway Projects - Alfan, Ervina (Asian Journal of Business and Accounting, 2010)
The Public-Private Partnership (PPP) concept was introduced and hailed as an effective mechanism to increase the efficiency of the public infrastructure provision as well as to achieve cost-effectiveness. However, the growing literature on PPP finds that the implementation of the PPP approach in infrastructure provision is costly and needs a high amount of state financial support. This study examines the cost of financing of the Malaysian PPP tolled highways, and the existence of government financial support to the concession companies. The results of this study show that private financing in the provision of infrastructure projects is more costly as opposed to public financing and a substantial amount of financial support from the government is required in implementing the PPP projects.